(untitled) (Journal of the College of Basic Education, 2025)
introduction and the importance of the research, where the importance of the research lies in the students’ motor anticipation and finding the relationship between it and the students’ accuracy skill in futsal. As for the research problem, through the researchers’ follow-up of middle school students and watching practical football lessons, they noticed that there is a fluctuation in learning skills. Including the scoring skill of students and as a result of the importance of this skill, the researchers decided to study this problem and shed light on the relationship between motor anticipation and the accuracy of the scoring skill of football for students. The aim of the research is to identify the relationship between motor anticipation and the accuracy of the scoring skill of football for students. The research community is represented by second-grade middle school students (70) students, while the research sample consisted of(20) Students and the results were extracted using the appropriate statistical processor to reach the results and then the results were presented, analyzed and discussed and the researchers reached the most important conclusions - the existence of a significant correlation between motor anticipation and the accuracy of the scoring skill in futsal for students. Motor anticipation qualifies the student in football to perform skills, including the skill of scoring well and finishing the attack. Based on the results reached by the research, the researchers They recommend a set of recommendations that emphasize the development of motor anticipation in the research sample because it is linked to the performance of the most important skills in football, and work on conducting more periodic and continuous tests to evaluate the scoring skill in futsal.